Active-inactive element co-coated sodium electric precursor as well as preparation method and application thereof
By co-covering active and inactive elements on the surface of the sodium-electric precursor, the problem of insufficient structural stability and energy density of the positive electrode material of sodium ion battery is solved, and higher capacity, rate performance and cycle life are achieved.
Patent Information
- Application Number
- CN202411906238.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The positive electrode material of sodium ion battery has shortcomings in terms of structural stability and energy density, and it is difficult to meet the needs of high stability and high capacity at the same time.
By co-covering active elements (such as copper ions) and inactive elements (such as zinc) on the surface of the sodium-electric precursor, lattice parameters are optimized, conductivity and sodium ion diffusion characteristics are improved, and the structural stability of the material is enhanced.
It achieves higher capacity, excellent rate performance and more stable cycle life of sodium ion battery materials, improving the overall performance of the battery.
Smart Images

Figure CN119706974A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to an active-inactive element co-coated sodium battery precursor and a preparation method and application thereof. Background Art
[0002] Electrochemical energy storage technology is the key to developing high-performance, sustainable energy storage systems, and secondary batteries, as the core component of this technology, play an indispensable role in large-scale energy storage. Lithium-ion batteries have shown great application potential in the energy storage industry due to their excellent energy density, long service life and excellent charge and discharge rates. However, problems such as the uneven distribution of lithium resources, fluctuations in lithium prices and limited resource reserves have gradually become bottlenecks restricting their development. At the same time, sodium-ion batteries, which are abundant in resources, widely distributed and low in cost, have begun to receive widespread attention and become a potential technology to replace lithium-ion batteries.
[0003] Since the radius of sodium ions is larger than that of lithium ions, sodium ion batteries face a series of challenges, such as limited structural stability: sodium ions can easily cause changes in the structure of the host material during the insertion and extraction process, which may ultimately lead to a reduction in the cycle life of the material; such as phase change: during the charging and discharging process, it may cause phase changes in the positive electrode material, resulting in battery capacity attenuation and voltage lag.
[0004] Therefore, improving the stability of the sodium-ion battery material structure and alleviating phase change are of great significance for the preparation of sodium-ion battery positive electrode materials with excellent cycle performance and safety performance. Among them, by constructing a stable and uniform coating layer on the surface of the positive electrode material, the stability can be effectively improved, the direct contact between the material and the electrolyte can be weakened, and the phase change and other problems can be alleviated, thereby improving the overall performance of the material.
[0005] For example, CN 118272922A coated the surface of the nickel-iron-manganese precursor with zinc source and / or aluminum source to obtain a precursor with surface-coated hydroxide, which effectively improved the structural stability of the sodium ion positive electrode material and suppressed the side reaction between the positive electrode material and the electrolyte, thereby significantly improving the material's cycle stability and rate performance. For example, CN 115377392A coated the surface of the layered oxide using a solid phase method, and obtained a coated sodium ion layered oxide after sintering, which improved the air stability of the positive electrode material, suppressed the occurrence of side reactions during the cycle, and also improved the conductivity.
[0006] However, the above-mentioned coating process includes single coating and co-doping coating, and the precursor is coated by co-precipitation and solid phase sintering and other technologies. Therefore, some of the positive electrode materials of sodium ion batteries increase their capacity by sacrificing stability, while others enhance their stability by reducing capacity. However, this trade-off makes it difficult to simultaneously meet the dual needs of sodium ion batteries for high stability and high capacity in energy storage applications, and it is difficult to maintain the specific capacity and stability of sodium ion battery materials at the same time.
[0007] Based on the above research, it is necessary to provide a sodium battery precursor that can bring higher capacity, excellent rate performance and more stable cycle life, so that the layered oxide positive electrode material of the sodium ion battery has both higher stability and energy density. Summary of the invention
[0008] The purpose of the present invention is to provide an active-inactive element co-coated sodium battery precursor and a preparation method and application thereof. The sodium battery precursor can not only optimize lattice parameters, improve electrical conductivity and sodium ion diffusion characteristics, and perform charge compensation by co-coating active elements and inactive elements on its surface, but also enhance the structural stability of the material, thereby ensuring the capacity of the battery and improving the rate performance and cycle performance of the battery.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a sodium-electrode precursor co-coated with active and inactive elements, wherein the sodium-electrode precursor co-coated with active and inactive elements comprises a core and a shell on the surface of the core, wherein the core comprises Ni x Fe y Mn z (OH) 2 , where x+y+z=1, 0.1≤x<0.4, 0.2≤y<0.7, 0.2≤z<0.4;
[0011] The housing includes M 1 and M 2 The hydroxide, the M 1 Includes any one of Cu, Fe or Co or a combination of at least two thereof, wherein the M 2 The metal includes any one of Mg, Al, Ti or Zn or a combination of at least two of them.
[0012] The surface of the precursor material of the present invention is co-coated with active elements and inactive elements, wherein active elements such as copper ions can optimize lattice parameters to a certain extent, improve electrical conductivity and sodium ion diffusion characteristics, and can also provide charge compensation (Cu 3+ / Cu 2+) improves the specific capacity of the battery, while enhancing the stability of the nickel-iron-manganese core, and the material with the introduction of active ions exhibits better rate performance at high current density; inactive elements such as zinc cannot provide reversible capacity due to their own inert chemical properties, but can enhance the structural stability of the material, reduce volume expansion and structural decay during the charge and discharge process, thereby improving the cycle stability and safety of the battery. Therefore, the present invention utilizes the synergistic effect of active elements and inactive elements to effectively provide the cycle performance and rate performance of the positive electrode material.
[0013] Preferably, the M 1 Including Cu, the M 2 Including Zn.
[0014] The active element of the present invention is preferably Cu, and the inactive element is preferably Zn. The two can not only play their respective roles, but also play a synergistic role. Compared with other elements, since the Cu element is an element with abundant resources, non-toxicity and low cost, the cost can be reduced. The Cu element also helps to improve the conductivity. The rate performance of the positive electrode material is affected by the conductivity, and the rate performance can be improved by increasing the conductivity. The introduction of the Cu element can enhance the stability. Compared with other inactive elements, the equilibrium constants of Zn and Cu hydroxide are less different, and co-precipitation is easy to achieve in the shell. Therefore, the shell of the present invention is preferably a copper-zinc coating layer.
[0015] Preferably, in the housing, M 1 and M 2 The molar ratio is 1:(0.5-2), for example, it can be 1:0.5, 1:1, 1:1.5 or 1:2, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] The active element and the inactive element in the shell of the present invention are within a specific molar ratio range, which can promote the synergistic effect of the two elements and improve the comprehensive performance of the sodium ion battery, and the shell is further preferably CuZn(OH) 2 .
[0017] Preferably, the molar ratio of the core to the shell is (90-98):(2-10), for example, 90:10, 95:5 or 98:2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In a second aspect, the present invention provides a method for preparing a sodium electrode precursor co-coated with active and inactive elements as described in the first aspect, the preparation method comprising the following steps:
[0019] (1) passing a first mixed metal salt solution, a first complexing agent solution and a precipitant solution into a base solution to perform a first coprecipitation reaction to prepare a core;
[0020] The first mixed metal salt solution includes a formulated amount of nickel ions, manganese ions and iron ions;
[0021] (2) After the inner core is prepared in step (1), the first mixed metal salt solution in step (1) is replaced with a second mixed metal salt solution, and a second coprecipitation reaction is continued to obtain the active-inactive element co-coated sodium electrode precursor;
[0022] The second mixed metal salt solution includes M 1 Ion and M 2 ion.
[0023] The present invention adopts a one-step co-precipitation method to prepare a sodium electrode precursor co-coated with active and inactive elements. The active and inactive elements are evenly distributed in the precursor coating layer prepared by the method, and the coating layer can prevent the nickel-iron-manganese core from being oxidized. Compared with solid-phase sintering coating, it is easier to regulate the distribution of active elements and inactive elements, and core-shell phase separation can be avoided as much as possible.
[0024] Preferably, after the inner core is prepared in step (1), the first mixed metal salt solution in step (1) is replaced by a second mixed metal salt solution, and the first complexing agent solution is replaced by a second complexing agent solution, so that the second mixed metal salt solution, the second complexing agent solution and the precipitant solution continue to undergo a second co-precipitation reaction.
[0025] When preparing the shell, the present invention also replaces the first complexing agent solution ammonia with the second complexing agent solution ascorbic acid, which is beneficial to the uniform distribution of the shell elements.
[0026] Preferably, the first complexing agent solution in step (1) comprises aqueous ammonia.
[0027] Preferably, the second complexing agent solution comprises ascorbic acid.
[0028] Preferably, the concentration of the second complexing agent solution is 0.01-0.1 mol / L, for example, it can be 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, 0.07 mol / L, 0.09 mol / L or 0.1 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the pH of the base solution in step (1) is 7-11.5, for example, 7, 8, 9, 10, 11 or 11.5, and the concentration of the first complexing agent is 3-25 g / L, for example, 3 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L or 25 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the feed rate of the first mixed metal salt solution in step (1) is 2-50 L / h, for example, 2 L / h, 10 L / h, 20 L / h, 30 L / h, 40 L / h or 50 L / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the feed rate of the precipitant solution in step (1) is 1-20 L / h, for example, 1 L / h, 5 L / h, 10 L / h, 15 L / h or 20 L / h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] Preferably, the feeding rate of the first complexing agent solution in step (1) is 0.4-10 L / h, for example, 0.4 L / h, 5 L / h or 10 L / h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the temperature of the first coprecipitation reaction in step (1) is 20-80°C, for example, 20°C, 40°C, 60°C or 80°C, the stirring speed is 100-350r / min, for example, 100r / min, 200r / min, 300r / min or 350r / min, and the pH is maintained in the range of 7-11, for example, 7, 8, 9, 10 or 11, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0034] Preferably, the first coprecipitation reaction in step (1) and the second coprecipitation reaction in step (2) are both carried out in a protective gas.
[0035] Preferably, the total metal ion concentration of the first mixed metal salt solution in step (1) and the second mixed metal salt solution in step (2) is independently 0.3-5 mol / L, for example, 0.3 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] Preferably, the concentration of the precipitant solution in step (1) is 5-15 mol / L, for example, 5 mol / L, 10 mol / L or 15 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the concentration of the first complexing agent solution in step (1) is 1-4 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L or 4 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Preferably, the feed rate of the second mixed metal salt solution in step (2) is 2-30 L / h, for example, 2 L / h, 5 L / h, 10 L / h, 15 L / h, 20 L / h, 25 L / h or 30 L / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, when the second coprecipitation reaction is carried out in step (2), the feed rate of the precipitant solution is 1-12 L / h, for example, 1 L / h, 5 L / h, 10 L / h or 12 L / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, when the second coprecipitation reaction is carried out in step (2), the feed rate of the second complexing agent solution is 0.3-8 L / h, for example, it can be 0.3 L / h, 2 L / h, 4 L / h, 6 L / h or 8 L / h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] Preferably, the temperature of the second coprecipitation reaction in step (2) is 30-80°C, for example, 30°C, 50°C, 70°C or 80°C, the stirring speed is 100-280r / min, for example, 100r / min, 150r / min, 200r / min, 250r / min or 280r / min, and the pH is in the range of 7-10, for example, 7, 8, 9 or 10, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] In a third aspect, the present invention provides a sodium ion battery positive electrode material, which is obtained by mixing and sintering a sodium source and a sodium battery precursor co-coated with active-inactive elements as described in the first aspect.
[0043] Preferably, the sintering is carried out at a temperature of 750-1200°C, such as 750°C, 900°C, 1100°C or 1200°C, for 5-25h, such as 5h, 10h, 15h, 20h or 25h, in an oxygen atmosphere.
[0044] In a fourth aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material as described in the third aspect.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The surface of the sodium electrode precursor of the present invention is co-coated with active elements and inactive elements. The inactive elements inhibit Na vacancies, promote Na diffusion, and inhibit the occurrence of phase change. The active elements can also provide charge compensation, effectively inhibit the change of the bulk structure, and maintain the order of the transition metal to improve the air stability.
[0047] (2) The sodium electrolyte precursor of the present invention is prepared by a co-precipitation method. The active elements and inactive elements in the shell of the precursor prepared by this method are evenly distributed, and the shell can prevent the nickel-iron-manganese core from being oxidized. Compared with solid-phase sintering coating, it is easier to control the distribution of active elements and inactive elements, and the core-shell phase separation can be avoided as much as possible. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a SEM image of the sodium electrode precursor co-coated with active and inactive elements as described in Example 1 of the present invention at a scale of 5 μm;
[0049] Figure 2 This is a SEM image of the sodium electrolyte precursor co-coated with active and inactive elements as described in Example 1 of the present invention at a scale of 10 μm. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0051] Example 1
[0052] This embodiment provides a sodium electrode precursor co-coated with active and inactive elements, including a core and a shell on the surface of the core, wherein the core includes Ni 0.34 Fe 0.33 Mn 0.33 (OH) 2 , the shell includes CuZn(OH) 2 , the molar ratio of the core to the shell is 0.9:0.1;
[0053] The preparation method of the active-inactive element co-coated sodium electrode precursor comprises the following steps:
[0054] (1) mixing nickel, iron and manganese sulfate solutions in different molar ratios to obtain a mixed metal salt solution A with a total metal ion concentration of 2 mol / L, wherein the molar ratio of nickel ions, iron ions and manganese ions is 0.34:0.33:0.33;
[0055] A mixed metal salt solution A, a 5 mol / L sodium hydroxide solution and an 8 mol / L ammonia water were added in parallel to a base liquid with a pH value of 11.0 and an ammonia concentration of 25 g / L. During the parallel addition, the feed rate of the mixed metal salt solution A was 40 L / h. The pH value of the reaction system was controlled between 10.0 and 11.0, and the ammonia concentration was controlled between 0.7 and 1.0 mol / L by controlling the flow rates of the sodium hydroxide solution and the ammonia water. Under nitrogen protection, a coprecipitation reaction was carried out at a reaction temperature of 52° C. and a rotation speed of 350 rpm. The reaction was continued for 60 hours. When the average particle size reached 5.0 μm, the reaction was stopped to obtain a core.
[0056] (2) preparing a mixed metal salt solution B containing 0.6 mol / L copper sulfate and 0.6 mol / L zinc sulfate, 5 mol / L sodium hydroxide solution, and 0.02 mol / L ascorbic acid solution; continuing to add the mixed metal salt solution B, ascorbic acid solution, and sodium hydroxide solution to the nickel-iron-manganese hydroxide slurry obtained in step (1), turning on nitrogen and the reactor stirrer, maintaining the stirring speed at 350 rpm, the temperature at 45° C., the flow rate of the mixed metal salt solution B at 40 L / h, controlling the concentration of ascorbic acid at 5 g / L during the synthesis process, adjusting the flow rate of the sodium hydroxide solution to control the reaction pH at 10, and stopping the feeding after continuously adding the raw materials for 5 hours, and forming a copper-zinc hydroxide shell with a thickness of about 1 μm on the surface of the inner core.
[0057] (3) Product post-treatment: After the reaction is completed, the product is centrifuged and washed, and then dried at 120° C. to obtain the sodium electrode precursor co-coated with the active and inactive elements.
[0058] The SEM image of the active-inactive element co-coated sodium electrode precursor prepared in this embodiment is as follows: Figure 1 and Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that the precursor has good sphericity and uniform particle size.
[0059] Example 2
[0060] This embodiment provides a sodium electrode precursor co-coated with active and inactive elements, including a core and a shell on the surface of the core, wherein the core includes Ni 0.34 Fe 0.33 Mn 0.33 (OH) 2 , the shell includes CuZn(OH) 2 , the molar ratio of the core to the shell is 0.9:0.1;
[0061] The preparation method of the active-inactive element co-coated sodium electrode precursor comprises the following steps:
[0062] (1) mixing nickel-iron-manganese sulfate solutions in different molar ratios to obtain a mixed metal salt solution A with a total metal ion concentration of 1.5 mol / L, wherein the molar ratio of nickel ions, iron ions and manganese ions is 0.34:0.33:0.33;
[0063] A mixed metal salt solution A, a 5 mol / L sodium hydroxide solution and an 8 mol / L ammonia water were added in parallel to a base liquid with a pH value of 11.5 and an ammonia concentration of 25 g / L. During the parallel addition, the feed rate of the mixed metal salt solution A was 40 L / h. The pH value of the reaction system was controlled between 10.0 and 11.0, and the ammonia concentration was controlled between 0.7 and 1.0 mol / L by controlling the flow rates of the sodium hydroxide solution and the ammonia water. Under nitrogen protection, a coprecipitation reaction was carried out at a reaction temperature of 52° C. and a rotation speed of 350 rpm. The reaction was continued for 60 hours. When the average particle size reached 5.0 μm, the reaction was stopped to obtain a core.
[0064] (2) preparing a mixed metal salt solution B containing 0.3 mol / L copper sulfate and 0.3 mol / L zinc sulfate, 3 mol / L sodium hydroxide solution, and 0.04 mol / L ascorbic acid solution; continuing to add the mixed metal salt solution B, ascorbic acid solution, and sodium hydroxide solution to the nickel-iron-manganese hydroxide slurry obtained in step (1), turning on nitrogen and the reactor stirrer, maintaining the stirring speed at 350 rpm, maintaining the temperature at 45° C., the flow rate of the mixed metal salt solution B at 40 L / h, controlling the concentration of ascorbic acid to 7 g / L during the synthesis process, adjusting the flow rate of the sodium hydroxide solution to control the reaction pH to 9.5-10, and stopping the feeding after continuously adding the raw materials for 8 hours, and forming a copper-zinc hydroxide shell with a thickness of about 1 μm on the surface of the inner core.
[0065] (3) Product post-treatment: After the reaction is completed, the product is centrifuged and washed, and then dried at 120° C. to obtain the sodium electrode precursor co-coated with the active and inactive elements.
[0066] Example 3
[0067] This embodiment provides a sodium-ion battery precursor co-coated with active and inactive elements. The sodium-ion battery precursor co-coated with active and inactive elements includes CoZn(OH) 2 Except for this, the rest are the same as in Example 1.
[0068] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the copper sulfate in step (2) is replaced by cobalt chloride.
[0069] Example 4
[0070] This embodiment provides a sodium-ion battery precursor co-coated with active and inactive elements. The sodium-ion battery precursor co-coated with active and inactive elements includes FeZn(OH) 2 Except for this, the rest are the same as in Example 1.
[0071] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the copper sulfate in step (2) is replaced by ferrous sulfate.
[0072] Example 5
[0073] This embodiment provides a sodium-ion battery precursor co-coated with active and inactive elements. The sodium-ion battery precursor co-coated with active and inactive elements includes CuMg(OH) in the outer shell. 2 Except for this, the rest are the same as in Example 1.
[0074] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the zinc sulfate in step (2) is replaced by magnesium sulfate.
[0075] Example 6
[0076] This embodiment provides an active-inactive element co-coated sodium electrolyte precursor. The active-inactive element co-coated sodium electrolyte precursor is the same as that of Embodiment 1 except that the shell includes copper aluminum hydroxide.
[0077] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the zinc sulfate in step (2) is replaced with aluminum sulfate.
[0078] Example 7
[0079] This embodiment provides an active-inactive element co-coated sodium electrolyte precursor, which is the same as Embodiment 1 except that the shell includes copper zinc hydroxide with a molar ratio of copper ions to zinc ions of 1:2.
[0080] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the concentration of copper sulfate in step (2) is 0.4 mol / L and the concentration of zinc sulfate is 0.8 mol / L.
[0081] Example 8
[0082] This embodiment provides an active-inactive element co-coated sodium electrolyte precursor, which is the same as Embodiment 1 except that the shell includes copper zinc hydroxide with a molar ratio of copper ions to zinc ions of 1:3.
[0083] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the concentration of copper sulfate in step (2) is changed to 0.3 mol / L and the concentration of zinc sulfate is changed to 0.9 mol / L.
[0084] Example 9
[0085] This embodiment provides an active-inactive element co-coated sodium electrolyte precursor, which is the same as Embodiment 1 except that the shell includes copper zinc hydroxide with a molar ratio of copper ions to zinc ions of 1:0.5.
[0086] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the concentration of copper sulfate in step (2) is 0.8 mol / L and the concentration of zinc sulfate is 0.4 mol / L.
[0087] Example 10
[0088] This embodiment provides an active-inactive element co-coated sodium electrolyte precursor, which is the same as Embodiment 1 except that the shell includes copper zinc hydroxide with a molar ratio of copper ions to zinc ions of 1:0.3.
[0089] The method for preparing the sodium electrolyte precursor described in this embodiment is the same as that of Example 1, except that the concentration of copper sulfate in step (2) is 0.9 mol / L and the concentration of zinc sulfate is 0.3 mol / L.
[0090] Comparative Example 1
[0091] This comparative example provides a sodium battery precursor, which is the same as Example 1 except that the surface of the sodium battery precursor does not include a shell.
[0092] The sodium electrolyte precursor described in this comparative example is the same as that of Example 1 except that step (2) is not performed.
[0093] Comparative Example 2
[0094] This comparative example provides a sodium battery precursor, which is the same as Example 1 except that the shell does not contain Cu.
[0095] The preparation method of the sodium electrolyte precursor material in this comparative example is the same as that in Example 1 except that the mixed metal salt solution B in step (2) does not contain copper ions.
[0096] Comparative Example 3
[0097] This comparative example provides a sodium battery precursor, which is the same as Example 1 except that the shell does not contain Zn.
[0098] The preparation method of the sodium electrode precursor material in this comparative example is the same as that in Example 1 except that the mixed metal salt solution B in step (2) does not contain zinc ions.
[0099] The sodium electric precursor obtained in the above embodiment and comparative example was mixed evenly with sodium carbonate in a molar ratio of 1:1.08, calcined at 1000°C for 16 hours, and ground and sieved to obtain a coated sodium ion battery positive electrode material. The positive electrode material prepared above was used as the positive electrode main material, and the metal sodium sheet was used as the negative electrode. They were assembled into CR2032 button batteries, and then electrochemical performance tests were performed within a voltage range of 1.5-4.0V, and then cycled 500 times at 1C / 5C. The test results are shown in Table 1 below:
[0100] Table 1
[0101]
[0102]
[0103] From Table 1 we can see that:
[0104] It can be seen from Example 1 and Comparative Examples 1-3 that the surface of the core of the present invention is coated with hydroxides of active elements and inactive elements, which can improve the capacity, rate performance and cycle performance of the battery, while the sodium-based precursor without co-coating of Cu and Zn elements will make the battery capacity, rate performance and cycle performance poor. It can be seen that the sodium-ion battery prepared from the precursor material prepared by the present invention as a positive electrode material and then assembled has better capacity, rate performance and cycle performance than conventional sodium-ion batteries; It can be seen from Example 1 and Examples 3-6 that the active element of the present invention is preferably Cu, and the inactive element is preferably Zn, which can further enhance the synergistic effect of the active element and the inactive element, and further ensure the comprehensive performance of the sodium-ion battery; It can be seen from Examples 1 and Examples 7-10 that in the shell of the present invention, the molar ratio of the active element and the inactive element is preferably within a specific range, which can ensure the performance of their respective effects on the one hand, and promote the synergistic effect of the two on the other hand, thereby further improving the comprehensive performance of the sodium-ion battery.
[0105] In summary, the present invention provides an active-inactive element co-coated sodium battery precursor and a preparation method and application. The sodium battery precursor can not only optimize the lattice parameters, improve the electrical conductivity and sodium ion diffusion characteristics, and perform charge compensation by co-coating the active element and the inactive element on its surface, but also enhance the structural stability of the material, thereby ensuring the capacity of the battery and improving the battery's rate performance and cycle performance.
[0106] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium electrode precursor co-coated with active and inactive elements, characterized in that: The active-inactive element co-coated sodium precursor comprises a core and a shell on the surface of the core, wherein the core comprises Ni x Fe y Mn z (OH)2, wherein x+y+z=1, 0.1≤x<0.4, 0.2≤y<0.7, 0.2≤z<0.4; The shell includes hydroxides of M1 and M2, wherein M1 includes any one of Cu, Fe or Co or a combination of at least two thereof, and M2 includes any one of Mg, Al, Ti or Zn or a combination of at least two thereof.
2. The active-inactive element co-coated sodium electrode precursor according to claim 1, characterized in that: The M1 includes Cu, and the M2 includes Zn; Preferably, in the shell, the molar ratio of M1 to M2 is 1:(0.5-2); Preferably, the molar ratio of the core to the shell is (90-98):(2-10).
3. A method for preparing a sodium electrode precursor co-coated with active and inactive elements as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) passing a first mixed metal salt solution, a first complexing agent solution and a precipitant solution into a base solution to perform a first coprecipitation reaction to prepare a core; The first mixed metal salt solution includes a formulated amount of nickel ions, manganese ions and iron ions; (2) After the inner core is prepared in step (1), the first mixed metal salt solution in step (1) is replaced with a second mixed metal salt solution, and a second coprecipitation reaction is continued to obtain the active-inactive element co-coated sodium electrode precursor; The second mixed metal salt solution includes M1 ions and M2 ions.
4. The preparation method according to claim 3, characterized in that: After the inner core is prepared in step (1), the first mixed metal salt solution in step (1) is replaced with a second mixed metal salt solution, and the first complexing agent solution is replaced with a second complexing agent solution, so that the second mixed metal salt solution, the second complexing agent solution and the precipitant solution continue to undergo a second coprecipitation reaction; Preferably, the first complexing agent solution in step (1) comprises aqueous ammonia; Preferably, the second complexing agent solution comprises ascorbic acid.
5. The preparation method according to claim 3 or 4, characterized in that: The pH of the base solution in step (1) is 7-11.5, and the concentration of the first complexing agent is 3-25 g / L; Preferably, the feeding rate of the first mixed metal salt solution in step (1) is 2-50 L / h; Preferably, the feed rate of the precipitant solution in step (1) is 1-20 L / h; Preferably, the feed rate of the first complexing agent solution in step (1) is 0.4-10 L / h.
6. The preparation method according to any one of claims 3 to 5, characterized in that: Step (1) The temperature of the first coprecipitation reaction is 20-80° C., the stirring speed is 100-350 r / min, and the pH is maintained in the range of 7-11; Preferably, the first coprecipitation reaction in step (1) and the second coprecipitation reaction in step (2) are both carried out in a protective gas.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The total metal ion concentration of the first mixed metal salt solution in step (1) and the second mixed metal salt solution in step (2) is independently 0.3-5 mol / L; Preferably, the concentration of the precipitant solution in step (1) is 5-15 mol / L; Preferably, the concentration of the first complexing agent solution in step (1) is 1-4 mol / L.
8. The preparation method according to any one of claims 3 to 7, characterized in that: Step (2) the feeding rate of the second mixed metal salt solution is 2-30 L / h; Preferably, during the second coprecipitation reaction in step (2), the feed rate of the precipitant solution is 1-12 L / h; Preferably, during the second coprecipitation reaction in step (2), the feeding rate of the second complexing agent solution is 0.3-8 L / h; Preferably, the temperature of the second coprecipitation reaction in step (2) is 30-80° C., the stirring speed is 100-280 r / min, and the pH is in the range of 7-10.
9. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material is obtained by mixing and sintering a sodium source and a sodium battery precursor co-coated with active and inactive elements as described in claim 1 or 2.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of nickel-aluminum coated nickel-iron-manganese sodium ion precursor material
CN114291852A
Sodium positive electrode precursor material and preparation method and application thereof
CN115732674A
Sodium ion precursor material as well as preparation method and application thereof
CN116282228A
Manganese-based layered positive electrode material of sodium-ion battery with core-shell structure and preparation method of manganese-based layered positive electrode material
CN118299539A
Core-shell type sodium ion battery positive electrode material and preparation method and application thereof
CN118572084A